Atomically precise thiolate-protected gold nanoclusters: current advances in solar-powered photoredox catalysis. Issue 17 (25th April 2023) - Liang, Hao; Chen, Qing; Mo, Qiao-Ling; Wu, Yue; Xiao, Fang-Xing
Abstract : The latest developments in atomically precise gold nanocluster based photosystems for solar energy conversion are comprehensively summarized and elucidated. Abstract : Photocatalysis has been regarded as an emerging technology to convert renewable solar energy to chemical fuels, providing unprecedented opportunities for solving the deteriorating energy crisis and environmental issues in the future. In recent years, atomically precise gold nanoclusters, which have emerged as novel light-harvesting antennas possessing the merits of unique atomic stacking fashion, the quantum confinement effect, enriched catalytically active sites and a discrete energy band structure, have been drawing enormous attention in diverse fields. Despite the advancement, there is deficiency of a systematic, comprehensive, and insightful summary on the gold nanocluster-based photosystems to reinforce our fundamental understanding of the charge transport characteristics of metal nanoclusters in photocatalysis. Herein, our review summarizes the latest progress in gold nanocluster mediated photocatalysis and photoelectrocatalysis for diverse applications including non-selective photocatalytic organic pollutant mineralization, photocatalytic selective organic transformation, photocatalytic hydrogen generation, photocatalytic CO2 reduction, and photoelectrochemical (PEC) water splitting. Moreover, we discuss the underlying photocatalytic and PEC mechanisms associated with the energy band and electronic structure of gold nanoclusters. Finally, perspectives and challenges of gold nanocluster-based photosystems are outlined. It is anticipated that our review could inspire ideas on how to smartly utilize atomically precise metal nanoclusters for crafting high-efficiency photosystems towards solar energy conversion.